Speech Acts Across Cultures: A Comparative Study of Request, Refusal, and Apology in English and Mandarin - Devi Alvionita Alindra; Fithriani, Rahmah; Pardi, Pardi (ITScience (Information Technology and Science), 2025)
This study investigates how the speech acts of request, refusal, and apology are realized across two culturally and linguistically distinct languages: English and Mandarin. Grounded in speech act theory and contemporary approaches to politeness and facework, the research examines how interactional norms, sociocultural values, and contextual expectations shape speakers’ pragmatic choices. While existing scholarship has extensively analyzed these speech acts individually, cross-cultural studies that integrate all three within a unified comparative framework remain limited. To address this gap, the present study employs a qualitative, discourse-based methodology incorporating naturally occurring spoken interactions, documentary and digital media data, and contextual commentaries. Conversation Analysis (CA) and thematic analysis are used to explore linguistic strategies, sequential organization, and culturally embedded meanings.Findings reveal systematic contrasts in directness, mitigation, sequencing, and face-management orientations. English speakers tend to favor explicit forms, efficient sequencing, and concise justification, reflecting low-context communication norms. Mandarin speakers employ greater indirectness, elaborate mitigation, relational alignment, and self-effacement, consistent with high-context communication and face-sensitive cultural orientations. However, patterns also vary by setting, social distance, power relations, and communicative medium, demonstrating that pragmatic behavior is shaped by both cultural tendencies and situational constraints.The study contributes to cross-cultural pragmatics by offering a comparative, multi-layered account of how requests, refusals, and apologies are constructed and negotiated in English and Mandarin. The findings have implications for intercultural communication, language pedagogy, and the development of pragmatic competence among speakers navigating bilingual or multilingual environments.